Suppression of exosomal miR-199a-3p, a differentially expressed miRNA in steroid-induced osteonecrosis of the femoral head, promotes cell proliferation, osteogenesis, and angiogenesis while inhibiting dexamethasone-induced apoptosis - Xia, Tixiong; Yang, Chengbin; Li, Xi; Chen, Tong; Xu, Yingxing (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionSteroid-induced osteonecrosis of the femoral head (SONFH) is a progressive and debilitating disorder caused by excessive glucocorticoid exposure. Dysfunction of bone marrow mesenchymal stem cells (BMSCs) and their exosome (Exos)-mediated signal transduction plays a key role in SONFH; however, the exact pathways involved remain under active investigation.MethodsThe differential expression profiles of long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and messenger RNAs (mRNAs) related to the Exos-mediated pathway in Exos derived from human BMSCs (hBMSCs) of patients with SONFH and control patients were analyzed by next-generation sequencing (NGS). The miR‐199a‐3p was identified as a differentially expressed miRNA, and its expression in BMSCs and their corresponding Exos was subsequently validated using quantitative real-time polymerase chain reaction. A series of functional experiments then confirmed that miR-199a-3p modulated osteoblasts (OBs) and human umbilical vein endothelial cells (HUVECs) activities via the Exos-mediated pathway, including cell proliferation, apoptosis, osteogenesis, and angiogenesis, with or without exposure to high-dose dexamethasone (Dex).ResultsNGS results revealed a total of 6,953 differentially expressed ncRNAs, 260 differentially expressed miRNAs, 13,577 differentially expressed mRNAs were identified in hBMSCs from patients with SONFH compared to controls. In hBMSCs-Exos, 207 differentially expressed ncRNAs, 183 differentially expressed miRNAs, and 1,075 differentially expressed mRNAs were detected. Integrated analysis of transcripts expressed in both hBMSCs and hBMSCs-Exos identified 659 differentially expressed ncRNAs, 11 differentially expressed miRNAs, and 1,600 differentially expressed mRNAs. The results of bioinformatics analysis showed that these differentially expressed RNAs were involved in regulation of endocytosis, receptor-mediated endocytosis, response to extracellular stimuli, and bone mineralization. Furthermore, the validation results demonstrated that the suppression of miR-199a-3p promoted proliferation, osteogenesis, and angiogenesis, while inhibiting apoptosis of OBs and HUVECs activities and exposed to high-dose Dex.DiscussionThis study identified differential expression profiles of ncRNAs, miRNAs and mRNAs related to the Exos-mediated pathway in SONFH through integrated analysis, and further demonstrated the negative role of miR‐199a‐3p in SONFH, involving proliferation, osteogenesis, and angiogenesis, as well as the regulation of apoptosis of OBs and HUVECs exposed to high-dose Dex through the hBMSCs-Exos-mediated pathway. Therefore, targeting miR‐199a‐3p may enhance the therapeutic efficacy of Exos-based treatments for SONFH.